1968
DOI: 10.1136/thx.23.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic rupture of the oesophagus and stomach

Abstract: Thirty-nine cases of traumatic perforation of the oesophagus or stomach have been studied. Thirty-two of the perforations followed oesphagoscopy, five were 'spontaneous,' and two were due to damage by a foreign body. Eight of the perforations occurred in the cervical oesophagus, 22 in the thoracic portion, and nine were in either the abdominal oesophagus or the stomach. Treatment was of two types-either operative closure of the perforation or a conservative routine of intravenous fluids, parenteral antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

1970
1970
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…Traumatic perforation of the oesophagus is usually caused by instrumentation, foreign-body trauma or so-called spontaneous rupture 5. Of these, perforation during oesophagoscopy is the most common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic perforation of the oesophagus is usually caused by instrumentation, foreign-body trauma or so-called spontaneous rupture 5. Of these, perforation during oesophagoscopy is the most common.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, perforation during oesophagoscopy is the most common. The rigid metal oesophagoscope and the instruments used for oesophageal dilation are the principal causes of damage 5. The relatively recent fibre-optic endoscopes, although characterised by a much-reduced incidence of perforation, do not allow direct visual oesophageal dilation.…”
Section: Discussionmentioning
confidence: 99%
“…As soon as the diagnosis is suspected, broad spectrum antibiotic treatment should be commenced. Thoracotomy on the appropriate side provides adequate access in most cases, but in a low perforation extending below the diaphragm a left thoracoabdominal approach has advantages (Craddock, 1968). For subphrenic extraperitoneal perforations without extension of the rupture above the diaphragm, however, a purely abdominal approach cannot be Mayer et al (1977) reported 5 cases of oesophageal perforation-3 spontaneous-with delayed recognition.…”
Section: Treatmentmentioning
confidence: 99%
“…So Innerhalb der 24-Stunden-Grenze und bei gutem Allgemeinzustand der Patienten ist möglichst unabhängig von der Lokalisation und der Größe der Speiseröhren-perforation der operative Verschluß des Defektes anzustreben. Im Halsteil empfahlen zwar Craddock und Mitarbeiter (8), exspektativ konservativ zu behandeln, doch nach unseren Erfahrungen kommt es gerade im zervikalen Ösophagusbereich häufig entweder zu einer langstreckigen Aufschlitzung der Speiseröhre oder zu einer primär recht langen, oft bis in das obere Mediastinum hineinreichenden Via falsa durch das die Verletzung herbeiführende Instrument. Beide Umstände lassen von vornherein ein chirurgisches Vorgehen, Freilegung der Verletzungsstelle und deren Versorgung durch zweischichtige Naht, sinnvoller erscheinen.…”
unclassified
“…Durch die Anwendung wasserlöslicher, leicht resorbierbarer und gewebefreundlicher Kontrastmedien lassen sich zusätzliche Komplikationen vermeiden.Die Therapie einer iatrogenen Speiseröhrenverletzung richtet sich nach der Zeitspanne, die zwischen der Perforation und dem Einsetzen der Therapie verstrichen ist, nach dem Gesamtzustand des Patienten, nach dem Sitz des Defektes, nach begleitenden Komplikationen (Pneumothorax, Pleuritis oder Pleuraempyem, Peritonitis, Mediastinitis) und nach der Beschaffenheit der Speiseröhre bzw. nach der Art des Grundleidens, welches zu dem diagnostischen oder therapeutischen Eingriff an der Speiseröhre geführt hat (verschluckter Fremdkörper, benigne Ösophagusstenose, Karzinom).Wenn man bedenkt, daß nur in 13% der Fälle die Perforation während des Manipulierens am Ösophagus bemerkt wird(8), so läßt sich aus dieser Tatsache ableiten, daß in der Mehrzahl der Fälle eine mehr oder weniger lange Zeit zwischen Speiseröhrenperforation, deren Erkennung und Behandlung verstreicht. Je länger diese Spanne ist, desto ungünstiger werden die Voraussetzungen für einen therapeutischen Erfolg.…”
unclassified